EDUCATIONAL TECHNOLOGY OF FORMATION OF UNIVERSITY STUDENTS OF NON-LINGUISTIC SPECIALTIES READINESS TO FOREIGN LANGUAGE COMMUNICATION - Halytska, Maya M. (Educological discourse, 2015)
The article deals with the problem of definition and justification of the structural components of educational technology in the formation of university students of non-linguistic specialties readiness to foreign language communication; series stages of its implementation.